Photolysis of Dimethyl Phthalate via Microwave Discharge Electrodeless Iodine Lamp: Parameters, Feasibility and Mechanism - Zhao, Y.J.; Yan, C.; Gu, D.H.; He, J.; Hou, H.Q. (Asian Journal of Chemistry, 2013)
This study reports, the photolysis of dimethyl phthalate using 206.2 nm UV light emitted from a locally made novel microwave discharge electrodeless iodine lamp (MDEIL). Optimal preparation parameters of MDEIL were determined as follows: iodine amount, 0.5 mg; krypton pressure, 2 torr and input power, 65 W. Removal efficiency of dimethyl phthalate reached 97.5 % at 20 min irradiation time and 20 mg L-1 initial dimethyl phthalate concentration. A possible mechanism of the dimethyl phthalate photolysis may involve electron transition reactions and reactions with hydroxyl radicals. The intermediates were identified as phthalic acid and 2-hydroxyl acid methyl esters. Results from this study may help promote further studies on the feasibility of MDEIL to decompose more aqueous organic contaminants, including other refractory contaminants.